Differentiation of Mouse Embryonic Stem Cells into Ventral Foregut Precursors. (13th February 2018) - Rothová, Michaela; Hölzenspies, Jurriaan J.; Livigni, Alessandra; Villegas, Santiago Nahuel; Brickman, Joshua M.
Abstract: Anterior definitive endoderm (ADE), the ventral foregut precursor, is both an important embryonic signaling center and a unique multipotent precursor of liver, pancreas, and other organs. Here, a method is described for the differentiation of mouse embryonic stem cells (mESCs) to definitive endoderm with pronounced anterior character. ADE‐containing cultures can be produced in vitro by suspension (embryoid body) culture or in a serum‐free adherent monolayer culture. ESC‐derived ADE cells are committed to endodermal fates and can undergo further differentiation in vitro towards ventral foregut derivatives. © 2016 by John Wiley & Sons, Inc.